Alternate construction technologies for mass housing: Challenges to adoption in India - Ayush Kahre; Debarpita Roy; Triveni Prasad Nanda (Indian Council for Research on International Economic Relations (ICRIER), 2022)
Rapid urbanisation and economic growth will increase the demand for adequate housing in Indian cities. Mass housing projects can help cater to this need. However, building mass housing using conventional technology is slow, lacks quality and is detrimental for the environment. In contrast, more mechanised alternate construction technologies substantially reduce construction time, improve quality, produce less waste and consume less water. Recognising their potential, the Government of India has launched the Global Housing Technology Challenge programme under the Technology Sub-mission of the Pradhan Mantri Awas Yojana - Urban to mainstream the use of alternate construction technologies in mass housing projects. In this paper, we point out that attempts to increase the adoption of alternate construction technologies may not yield easy results. Based on semi-structured interviews with 40 experts and practitioners from the residential construction industry, government, academia, and civil society and a literature review, we find six major challenges to the adoption of alternate construction technologies for mass housing in India: (i) high initial investment, (ii) achieving optimal scale required for commercial viability, (iii) reorientation of planning and design, (iv) transportation of building components, (v) lack of skilled professionals, and (vi) consumer scepticism and questions on liveability. We conclude with an outlook on the adoption of these technologies and some ideas on improving their uptake.
Keywords: L74; L78; R38; 330; Construction technology; affordable housing; mass housing; GHTC; PMAY U; Lighthouse Projects; offsite construction; modular construction